PENGEMBANGAN MADRASAH DAN SEKOLAH ISLAM UNGGULAN - Mujtahid Mujtahid (el-hikmah, 2011)
Today many educational institutions in Indonesia which is developing a superior education system, including institutions of Islamic education. Islamic schools or madrasah are the flagship of Islamic educational institutions that create superior organizational culture and climate and effective. Development of pre-eminent organization of Islamic schools seem reflected in human resources (teachers, staff, and students) facilities, as well as other supporting facilities to produce graduates who are intellectually astute, have a certain spiritual sturdy. This paper has produced a review and new view on the development of madrasah and Islamic schools of excellence. To develop the pre-eminent Islamic schools or madrasah, are needed: (1) carrying capacity of an effective and functional, such as a superior human resources, facilities and infrastructure (classrooms representative, libraries and laboratories), support facilities (boarding, mosque). (2) Careful planning and mature designed in accordance with the vision, mission and objectives of the institutional school, requires analyzing the needs of academic and institutional systems, and understand the geographical and cultural context. (3) Building a shared commitment, and build mind set collectively, always give priority to continuous innovation, and utilizing information technology as an effective learning resource.